Sound patterning as a structural and classifying principle of literary folklore genres - Nikolić, Davor (2014)
This research was interested in establishing phonostylistic criteria for the classification of short folklore genres such as proverbs, verbal charms, curses, blessings, tongue-twisters and counting-out rhymes. Most of the previous research on these short literary forms emphasized sound patterning as an important structural quality, but only few have recognized its classifying potential. The researchers were also faced with the problem of semantics because some of these genres, especially tongue-twisters and counting-out rhymes, seemingly appear to be nonsense. On the other hand, semantics of curses and blessings is inseparable from their communication effect or their pragmatics. The old problem of sound-content relationship in poetry thus becomes extremely relevant when trying to define and classify short folklore genres. If sound patterning is one of the essential elements of poetry (at least in the traditional sense of the term), to such an extent where it cannot be simply described as an echo of sense, then it could be plausible to consider sound patterning as the primary and active principle for at least one part of short folklore genres (namely tongue-twisters and counting-out rhymes). Combining the relatively old term of phonetic (sound) symbolism with the contemporary phonosemantic linguistic theories these genres could be described as phonosemantic. In contrast, curses and blessings could then be described as pragmasemantic. The phonostylistic method was used to analyze phoneme frequency, sound repetitions (alliterations, assonances) and etymological figures (polyptotone, antanaclasis and paronomasia) in the corpus of Croatian short folklore genres. The results substantiate the idea of sound patterning as a classifying principle for distinguishing between phonosemantic and pragmasemantic genres.
Projekt MZOS
ENG